Diseminasi Snack Ternak Berbahan Baku Lokal (Berakal) Sebagai Solusi Pakan Berkualitas dan Ekonomis di Kabupaten Sigi - Ujang Kurniawan; Fanny Iswarini Nur T; Afrini Afrini; Dwi Putriana N. Kinding (Lembaga Pengembangan Kinerja Dosen, 2024)
Considering the abundance of underutilized local feed materials, particularly large amounts of agricultural waste that have yet to be optimized as a feed source, the production of feed snacks is expected to provide a solution for utilizing this waste. By adding local ingredients such as moringa leaves, which have highly potential nutritional content, the development of these feed snacks is further enhanced. Moringa leaves are a valuable commodity in terms of both their nutritional content and benefits when added to feed formulations, serving to complement the standardized nutrient requirements. Through a technological processing involving silage/fermentation and to facilitate application and increase storage life, the product is formed into snacks. Addressing the ongoing complaints of farmers regarding the need for feed with high protein content at an economical price, the BERAKAL livestock snack emerges as a solution to meet this demand. With an affordable price, it is expected to fulfill the needs of farmers who face a shortage of quality feed compared to commercial concentrates which are relatively more expensive. The methods of socialization and technical guidance typically involve several stages and strategies to enhance the competence and awareness of the community, such as initial socialization, training and technical guidance, and general technical guidance. BERAKAL livestock snacks can increase livestock productivity, leading to increased production of meat, milk, and eggs, and improving the competitiveness of Indonesian livestock products. BERAKAL livestock snacks can enhance the competitiveness of Indonesian livestock products in the global market. The BERAKAL livestock snack program has the potential to provide significant benefits to universities in terms of implementing MBKM and achieving IKU. Some of these benefits include increasing collaboration with industry partners and the community. This program will involve industry partners and the community in the development and marketing of BERAKAL livestock snacks. This collaboration can enhance the university's reputation as a reliable partner in developing products and services that benefit the community.